Statistics Made Simple For School Leaders : a new approach for using student, staff, and community data - Carroll, Susan Rovezzi; Carroll, David J., 1953- (Lanham, Maryland : Rowman & Littlefield Publishing Group, 2022)
"This book is a practical handbook for school leaders who want to use data to help understand their students, their staff and their communities, day to day"--
Includes bibliographical references and index.
Keywords: Educational statistics; School management and organization -- United States